Surface Mass Balance Controlled by Local Surface Slope in Inland Antarctica: Implications for Ice‐Sheet Mass Balance and Oldest Ice Delineation in Dome Fuji. Issue 24 (23rd December 2021) - Van Liefferinge, Brice; Taylor, Drew; Tsutaki, Shun; Fujita, Shuji; Gogineni, Prasad; Kawamura, Kenji; Matsuoka, Kenichi; Moholdt, Geir; Oyabu, Ikumi; Abe‐Ouchi, Ayako; Awasthi, Abhishek; Buizert, Christo; et al.
Abstract: The limited number of surface mass balance (SMB) observations in the Antarctic inland hampers estimates of ice‐sheet contribution to global sea level and locations with million‐year‐old ice. We present finely resolved SMB over the past three centuries in a low‐accumulation region with significant depth hoar formation on Dome Fuji derived from ∼1, 100 km of microwave radar stratigraphy dated with a firn core. The regional‐mean SMB over the past 264 years is estimated to ∼22.5 ± 3.3 kg m −2 a −1, but with large local variability of up to 30%. We found that local SMB is negatively correlated with surface slope at scales of a few hundred meters, resulting in anomalous zones of low SMB which represent as much as 8–10% of the total SMB on the inland plateau if the SMB‐slope relationship is more widely valid. This impact should be investigated further to improve estimates of Antarctic mass balance and sea‐level contribution. Plain Language Summary: Sampling the world's Oldest Ice (more than 1 million years) is crucial for understanding why pacing of glacier‐interglacial cycles has changed in the past. Such ice will be preserved at the base of the Antarctic ice‐sheet interior, though its location depends on many factors, including snow accumulation rate. We mapped snow accumulation in the Dome Fuji region, using radar‐detected snow layers dated with volcanic signals in ice cores. Although climate models indicate a very low and nearly uniform snow accumulation in this region, the observations show large variations of up to about 30% which we found to be related to local surface slope at a scale of a kilometer or less. This new knowledge contributes to better locate Oldest Ice and to improve estimates of ice‐sheet mass changes and its contributions to global sea level. Key Points: Ultrawide band microwave radar reveals spatially highly variable surface mass balance (SMB) over the past three centuries in inland Antarctica SMB anomalies resulting from local surface slopes may represent as much as 8–10% of the total SMB on the inland plateau The new SMB data have direct implications for the search for million‐year‐old ice in the Dome Fuji area, East Antarctica